ANALISIS TINGKAT KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI KANTOR PAJAK PRATAMA MANADO - Sondakh, Javier; Morasa, Jenny; Wokas, Heince (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
In accordance with the decision of the finance minister 34/PMK.03/2005 UN taxation philosophy about sharing property tax revenues between the central government and local governments that receive the proceeds of land and building tax is directed for the purpose of public interest, then the proceeds from the PBB constitutes acceptance of the State which must be shared between the central government and local governments. The purpose of this study was to determine the level of tax compliance in Target and Realization of Land and Building Tax payments. Sources of data used in this study is secondary data is data that comes from the Tax Office Primary service Manado. The results showed that the Land and Building Tax Revenue in theperiod of four years from 2008-2011 continued to increase except in the year 2009. In general, most people are aware of their obligations as citizens of Indonesia are good and they are aware that taxes are a form of public participation in local development to better developed and developing countries. Also there is a small community is not aware of its obligations as a taxpayer PBB.